Failure Modes and Fault Morphology - Adam J. Cawood; David A. Ferrill; Kevin J. Smart (Lithosphere)
Fault failure modes determine the geometric characteristics of faults and fault zones during their formation and early development. These geometric properties, in turn, govern a wide range of fault processes and behaviors, such as reactivation potential, fault propagation, and growth, and the hydraulic properties of faults and fault zones. Here, we use field data and close-range digital photogrammetry to characterize, in detail, the surface morphology of three normal faults with cm-scale displacements in mechanically layered carbonates of the Cretaceous Glen Rose Formation at Canyon Lake Gorge, Comal County, Texas. Analyses demonstrate complex fault surface geometries, a broad spectrum of slip tendency (Ts) and dilation tendency (Td), and variable failure behavior. We show that (i) fault patches coated with coarse calcite cement tend to have moderate to high dips, low to high Ts, and high to very high Td; (ii) slickensided fault patches exhibit low to moderate dips, moderate to very high Ts, and moderate to high Td; and (iii) slickolite patches exhibit low dips, moderate Ts, and low to moderate Td. Calcite-coated patches are interpreted to record hybrid extension-shear failure, whereas slickensided and slickolite patches record shear and compactional shear failure, respectively. Substantial variability in both Ts and Td across the exposed fault surfaces reflects complex fault morphology that is not easily measured using traditional field techniques but is captured by our photogrammetry data. We document complex fault geometries, with kinematic (displacement) compatibility indicating the various failure modes were active coevally during fault slip. This finding is in direct contrast with the often-assumed concept of faults forming by shear failure on surfaces oriented 30° to σ1. Distinct failure behaviors are consistent with patchworks of volume neutral, volume gain, and volume loss zones along the fault surfaces, indicating that the characterized faults likely represent dual conduit-seal systems for fluid flow.